The Effect of the CTL (Contextual Teaching and Learning) Learning Model on the Formation of Character Based on Local Wisdom Values (Mattabe) and Social Studies Learning Outcomes of Class V Students - Usriani Usriani; Rosleny B; Syarifuddin Cn Sida (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this research is to find out the description of Social Studies lesson content by applying the CTL (Contextual Teaching and Learning) learning model for Class V students; description of social studies learning outcomes with the application of the CTL (Contextual Teaching and Learning) learning model for Class V students; and the effect of the application of the CTL (Contextual Teaching and Learning) model on character formation based on local wisdom values ​​(Mattabe) and social studies learning outcomes for Class V students. This type of research is quantitative, descriptive inferential in this study given certain treatment, namely control class and experimental class. The sample in this study is part of the population with the sampling technique is random sampling. The data collection method used is a character building questionnaire based on local wisdom values ​​(mattabe) and a multiple choice test for student learning outcomes. The data analysis technique used is the first by using a descriptive statistical approach, prerequisite test, and Manova hypothesis testing. The results of the study, test the hypothesis using manova, with a sig value. is 0.000 < 0.05, then Ho is rejected and H1 is accepted, that is, there is a significant effect on the application of the CTL (Contextual Teaching and Learning) model to Character Building based on local wisdom values ​​(Mattabe) and social studies learning outcomes for Class V students